Climate policy in British Columbia: An unexpected journey - Fairbrother, Malcolm; Rhodes, Ekaterina (Frontiers in Climate, 2023)
Since introducing a path-breaking carbon tax in 2008, the western Canadian province of British Columbia (BC) has attracted significant attention from climate policy scholars. The enactment of its carbon tax has made the case of BC intriguing, as Canada is a poor climate performer, BC is a fossil fuel producer, and carbon taxes are politically challenging to introduce anywhere. This paper discusses the BC tax, and what lessons it holds for other jurisdictions. We complement existing accounts with new details about key events and developments in recent years, and about climate policymaking in BC generally. While there are features of the tax’s design and promotion that would be worth replicating elsewhere, we argue its survival reflects some simple good fortune. Moreover, the case of BC should not be reduced to its tax, as the province has enacted other notable climate policies, some of which have done more to reduce emissions while attracting less public criticism.